Impact of edible films as an alternative food packaging alternative - Nelssi Chamorro (2025)
This study evaluates the impact of edible films as a sustainable and biodegradable alternative for food packaging in response to increasing plastic pollution. The objective is to analyze the effectiveness of these films in sustainability, multifunctionality and food waste reduction. A systematic literature review (SLR) was conducted in scientific databases, selecting relevant studies published between 2019 and 2024 using specific criteria and PICOC, BIBLIOMETRIX and PRISMA methodologies. The results reveal that 64.29 % of the studies consider edible films to be beneficial, standing out not only for being biodegradable, but also for their ability to protect food, prolong its shelf life and reduce environmental contamination. In addition, their antimicrobial and antioxidant functionality is highlighted, using materials such as gelatin, chitosan and other natural polymers. In conclusion, edible films are a promising solution to reduce plastic pollution and improve food preservation, presenting themselves as an environmentally friendly alternative in the packaging industry. However, more research is needed to optimize their production and efficacy in various applications.